Research on Quantitative Evaluation and Influencing Factors of the Vitality of Newsstand – an example of Beijing - Wu Jingfen; Sheng Qiang; Li Xinyi (Lodz University of Technology Press, 2023)
Newspaper kiosks used to be cultural Windows of cities, but in the data era, they face many challenges of survival and problems of future renewal. At the micro level, this study obtained the total number of transactions of 25 existing kiosks and the number of transactions of each derivative function through field research and carried out a quantitative evaluation on the vitality of kiosks based on this. The paper further analyses the explanatory power of five parameters, including population density, commercial function, topological form, geometric form and street walkability, on the vitality of the existing newsstands. At the macro level, based on Baidu Street View time machine, this study obtained the spatiotemporal differentiation data of 277 newsstands in the western part of Beijing which covers an area of about 160 square kilometres (2013–2021) and compared the difference of the above five parameters of the death and the existing newsstand space in an eight-year time span. In this way, we can reveal the reasons that affect the vitality of the newsstand for a long time. It is found that the walkability and population density are the main factors affecting the vitality of newsstands, both in the existing newsstands and the newsstands within a period of eight years. In terms of each function, the correlation between the number of transactions of newspapers and periodicals and the number of transactions of life and retail functions and the two parameters of walkability and commercial function density are different. On this basis, the paper puts forward some strategies, such as function updating and space positioning updating, in order to provide reference for the demolition, construction and urban renewal of the newsstand in the future.
Keywords: newsstand; street walkability; space syntax; population density; kiosk z prasą; możliwość poruszania się po ulicach; składnia przestrzeni; gęstość zaludnienia